Design and validation of a new fixture for the shear testing of cellular solids - Diel, Sergej; Huber, Otto; Steinmann, Paul; Winter, Werner (Archive of Applied Mechanics, 2013)
The design and validation of a new fixture for the shear testing of cellular solids are presented. The fixture is an extended version of a picture-frame shear fixture (EPF) and is suited for comparatively thick rectangular block specimens. The stress state in the specimen is analyzed using a detailed finite element model. The finite element model is based on a 3D CAD model and incorporates friction in the revolute joints. Using specimens with low stiffness, a nearly pure and uniform shear stress state is induced in the specimen. A correction factor for the shear stress is derived which takes into account the friction in the joints and the nonuniformity of the shear stress distribution in the gauge section. The shear response of the polymer foam Rohacell® 200 WF is determined in order to demonstrate the capabilities of the EPF. The strain state is analyzed by means of digital image correlation and is detected to be very pure and uniform on the specimen’s surface, as predicted by the numerical analysis. The shear modulus obtained with the EPF is in good agreement with the calculated shear modulus derived from tensile tests on the same material. In addition, there is only little scatter of the strength values over the tested specimens which further confirms the accuracy of the new fixture.
UnivIS-Import:2015-03-09:Pub.2013.tech.FT.FT-TM.design
Keywords: Shear test fixture Shear modulus Shear strength Cellular solids Digital image correlation FEM Archive of Applied Mechanics Archive of Applied Mechanics Look Inside Other actions Export citation Register for Journal Updates About This Journal Reprints and Permissions Add to Papers Share Shear test fixture Shear modulus Shear strength Cellular solids Digital image correlation FEM Archive of Applied Mechanics Archive of Applied Mechanics Look Inside Other actions Export citation Register for Journal Updates About This Journal Reprints and Permissions Add to Papers Shear test fixture; Shear modulus; Shear strength; Cellular solids; Digital image correlation; FEM